ANÁLISIS DEL MÉTODO DE EVALUACIÓN MULTICRITERIO PARA EL DESPLIEGUE E IMPLANTACIÓN DEL FUTURO SISTEMA DE RADIOCOMUNICACIONES DIGITALES DE EMERGENCIA DEL ESTADO (SIRDEE) - Belda Esplugues, Enrique; Bernabeu Piñana, Eduardo (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2023)
Public safety communications, which to date have been based on narrowband technologies with voice as the main service to be provided, are undergoing a transformation towards broadband technologies thanks to the standardization of services oriented to this sector, such as group communications, which will make it possible to adopt new services that were only available in commercial networks such as multimedia communications or data exchange. At present, public safety networks have various deployment modes based on commercial, hybrid or dedicated networks. Apparently, if an analysis of the different options is not carried out, the conclusion could be that any of them is valid for implementing a public safety communications network. This article proposes a multi-criteria evaluation method as well as an analysis of the above options to conclude which is the most suitable modality to deploy a network of this type.